Team-based Care for Improving Hypertension Management Among Outpatients. (30th September 2020) - Santschi, V; Wuerzner, G; Pais, B; Chiolero, A; Schaller, P; Cloutier, L; Paradis, G; Burnier, M
Abstract: Background: Innovative models of care are needed to reduce poor blood pressure (BP) control in European countries. The TBC-HTA study evaluated the effects of an interprofessional team-based care (TBC) intervention, involving nurses, community pharmacists, and physicians, on BP control compared to usual care. Methods: We conducted a pragmatic randomized controlled study in ambulatory clinics and community pharmacies in Lausanne and Geneva, Switzerland (ClinicalTrials.gov: NCT02511093). Uncontrolled treated hypertensive patients were randomized to TBC (N = 46) or usual care (UC: N = 43). The TBC intervention was led over 6 months. Nurses and pharmacists met patients every 6 weeks to measure BP, assess lifestyle and medication adherence, and provide health education. After each visit, they wrote a report with recommendations to the physician who could adjust antihypertensive therapy accordingly. The outcome was ambulatory BP measured at 6 and 12 months. Results: A total of 60 men and 29 women [mean (SD) age: 61(12) year; mean (SD) number of antihypertensive drugs: 2 (1)] were included. At baseline, mean (SD) BP was 144(10)/90(8) and 147(12)/87(11) mmHg in the TBC and UC care groups. 76 patients were followed up to 12 months. At 6 months, the between-group difference in mean BP was -3/+2 mmHg [95% CI: -10 to + 5 / -2 to + 5]; BP control was 38% in the TBC group and 33% in the UC group, respectively. At 12 months, the between-group difference in mean BP was -8/-3 mmHg [95% CI: -14 to -1/-7 to + 1]; BP control was 34% in the TBC group and 20% in the UC group, respectively. Conclusions: This TBC intervention helped long-term BP control among hypertensive outpatients in Switzerland. In line with recent European guidelines (ESC/ESH), this type of care should be more widely implemented. Key messages: A TBC of hypertension helped control BP in a Swiss healthcare setting. Policymakers should evaluate how to implement such intervention.